Tradition vs. Administration: Challenging the Cultural Barriers to Marriage Registration in Indonesia - Arifin, Mochammad (Sakina: Journal of Family Studies, 2025)
The persistent issue of unrecorded marital status in population documents remains critical in many Indonesian villages, including Kebonagung Village, Blitar Regency. Observations reveal that over 90% of married couples in the village have not updated their marital status, impeding access to essential public services such as health insurance, social assistance, and school enrollment. This study adopts a micro-level, participatory qualitative approach—utilizing observation, in-depth interviews, and documentation—to explore the socio-cultural factors affecting administrative awareness. Findings indicate that legal illiteracy, the perception of administration as mere formality, limited outreach by village officials, and deeply rooted local customs are primary barriers to marriage registration. Despite the availability of service infrastructure and innovative programs like Salam Sak Jangkah and SAIDI (sedino dadi), these initiatives often fail due to inadequate community engagement and weak public communication. The study’s key contribution lies in highlighting that structural solutions alone are insufficient; effective strategies must integrate educational, cultural, and community-based dimensions. This research enriches the discourse on public administration and family law in rural contexts by emphasizing the role of local actors—religious leaders, officials, and citizens—in fostering legal awareness. However, the study is limited by its geographic focus on a single village and the underrepresentation of youth perspectives. Future research should adopt a comparative and mixed-methods approach to assess the broader applicability of community-driven interventions and measure their impact quantitatively.